Novel Inhibitors of Plasmodium falciparum Dihydroorotate Dehydrogenase with Anti-malarial Activity in the Mouse Model - Booker, Michael L. (American Society for Biochemistry and Molecular Biology, 2010)
Plasmodium falciparum, the causative agent of the most deadly form of human malaria, is unable to salvage pyrimidines and must rely on de novo biosynthesis for survival. Dihydroorotate dehydrogenase (DHODH) catalyzes the rate-limiting step in the pyrimidine biosynthetic pathway and represents a potential target for anti-malarial therapy. A high throughput screen and subsequent medicinal chemistry program identified a series of N-alkyl-5-(1H-benzimidazol-1-yl)thiophene-2-carboxamides with low nanomolar in vitro potency against DHODH from P. falciparum, P. vivax, and P. berghei. The compounds were selective for the parasite enzymes over human DHODH, and x-ray structural data on the analog Genz-667348, demonstrated that species selectivity could be attributed to amino acid differences in the inhibitor-binding site. Compounds from this series demonstrated in vitro potency against the 3D7 and Dd2 strains of P. falciparum, good tolerability and oral exposure in the mouse, and ED(50) values in the 4-day murine P. berghei efficacy model of 13–21 mg/kg/day with oral twice-daily dosing. In particular, treatment with Genz-667348 at 100 mg/kg/day resulted in sterile cure. Two recent analogs of Genz-667348 are currently undergoing pilot toxicity testing to determine suitability as clinical development candidates.